The influence of leader power on interpersonal conflict in the workplace / Rozilah Abdul Aziz ... [et al.] - Abdul Aziz, Rozilah; Noranee, Shereen; Hassan, Narehan; Hussein, Rohaya; Jacob, Gouri A. Domnic (Faculty of Business and Management, 2021)
Interpersonal conflict partly depends on the magnitude of power exercised by superiors in the workplace. The need to investigate how manager's power affects subordinates' interpersonal conflict is crucial so that managers can change or maintain their power to achieve optimum results in organizations. Hence, the purpose of this study is to examine the influence of leader power towards interpersonal conflict at Government Linked Companies (GLCs), Malaysia. A total of 388 questionnaires were distributed to employees of GLCs, Malaysia. A Structural Equation Modelling (SEM) analysis revealed that twenty-two percent of the variation in interpersonal conflict can be explained by the power possessed by managers. It also revealed there is a strong positive, linear and significant relationship between leader power and interpersonal conflict. Therefore, management should be concerned with the authority given to managers as power could lead to a devastating interpersonal conflict.